A theoretical study for increasing production of electric power from Iraqi steam power plants. - حاتم فلاح فاخر; حسن د.مؤيد رزوقي (Al-Khwarizmi Engineering Journal, 2017)
This article conclude a theoretical study for the possibility to produce additional electric power from Iraqi steam power plants by cutting – off high-pressure feed water heaters . Three separated steam power plants which Dura , south –Baghdad and Nasria were studied . The investigation showed the possibity of increasing the electric power from 10 to 15% for Dura and Nasria , whereas 6% for south – Baghdad . According to the nowadays of operation to Iraqi steam power plants , the results showed that by cutting–off high pressure feed water heaters we can generate additional electric power about 250 MW during 3-4 hrs. daily. In addition, the fuel consumption can be reduced in comparison with diesel generator, which is used to produce the same add- ional electric power.